Forage quality of species-rich mountain grasslands subjected to zero, PK and NPK mineral fertilization for decades - Ineichen, Simon; Marquardt, Svenja; Kreuzer, Michael; Reidy, Beat (Wiley, 2020)
To maintain species‐rich swards from which forage of a high nutritional quality can be produced, it is essential to adapt grassland fertilization strategies. In this study, we investigated how different long‐term mineral fertilization treatments affect dry‐matter (DM) yield, plant species composition, and nutrient and mineral concentrations of forage from mountain grasslands. During 2 years, forage was sampled from three different long‐term fertilization experiments located at 930 (L), 1,190 (M) and 1,340 (H) m a.s.l. at different sites in Switzerland. At each site, three mineral fertilization treatments (0, PK and NPK) had been maintained for three to six decades, with two (L and M) or three harvests (H) per year. Yield, the botanical composition and concentrations of net energy, utilizable crude protein and different phenolic fractions were determined. Nutrient and mineral concentrations were also determined. For all three sites (L, M and H), unfertilized swards had lower annual DM yields (3.39, 5.17 and 2.73 t/ha) compared to PK (6.33, 7.17 and 4.44 t/ha) and NPK fertilized swards (7.69, 7.22 and 7.44 t/ha), respectively. Long‐term fertilization had little effect on the gross nutrient and phenolic composition, but forage P and K concentration increased. The decades‐long fertilization of either PK or NPK of up to 85 kg N, 80 kg P2O5 and 240 kg K2O/ha reduced plant species richness only at site H. Fertilization of PK may allow to simultaneously increase forage productivity and maintain forage quality in mountain grasslands.